Lotus root (Nelumbo nucifera Gaertn) flour a novel ingredient for the formulation of traditional unleavened flatbread: Rheological, physical and nutritional characteristics, and sensory attributes. Issue 12 (5th November 2021) - Saeed, Syed Muhammad Ghufran; Ayesha, Rida; Ali, Syed Arsalan; Ali, Rashida; Ahmed, Rahil
Abstract: Lotus roots ( Nelumbo nucifera Gaertn ) is a naturally rich source of bioactive compounds that have been known for the prevention of numerous diseases. In the present study, lotus root flour (LRF) was substituted as a wheat flour (WF) at different concentrations (5%, 10%, 15%, 20%, and 25% w/w) and its effect on the functional properties, rheological characteristics, antioxidant activity, total phenolic content (TPC), physical properties, nutritional profile, and sensory attributes on flour and unleavened flatbread samples were evaluated. The results showed that lower quantity of gluten content was found in flour blends, which correlates with the high water absorption (WA) of LRF which interfere in the gluten network development. The mixing profile of the dough as studied using farinograph showed an increase in WA (64.80% to 77.19%), dough development time (7.16 to 10.38 min), and dough stability (5.21 to 7.22 min) with increase in the LRF amount. Whereas, pasting profile of the blends showed an increase in maximum viscosity (1, 152.11 to 1, 177.21 BU) and break down values (401.21 to 477.11 BU), although, the setback values (577.13 to 450.22 BU) decreased with the addition of LRF. Furthermore, flatbread supplemented with higher amount of LRF were found to be less elastic and stiffer in texture. However, there was an overall improvement in softness, rollability, and spreadability of dough up to 15% substitution. The crude fiber and ash contents of LRF‐WF flatbread samples were improved from to 0.31% to 3.87% and 0.95% to 1.89%, respectively. Their TPC increased from 14.43 to 74.16 mg GAE/100 g DW of sample. Although, baking decreased the TPC in comparison to flour blends. Sensory and textural performance exhibited that the unleavened flatbread samples were acceptable for substitution up to 15% LRF. Based on this study, LRF may be declared and commercialized as a highly antioxidative and nutritive edible flour, which can be prospectively used in the development of nutraceuticals and functional foods. Novelty impact statement: Lotus root is an underused vegetable with numerous pharmacological properties. The present study was one of the first of its kind as lotus root flour (LRF) has not been incorporated before in formulation of traditional unleavened flatbread. LRF‐enriched flatbread resulted in increased polyphenols, antioxidants and dietary fiber compared with control flatbread. Thus, increasing the nutraceutical value of our basic food, which ultimately address the health issues of consumers.